Islam Nusantara as a Counter-Discourse to Transnational Purification - Saiful Fallah; Nanda Ahmad Basuki; Mahbubi; Abd Shamad; Supra (Jurnal Pelita Raya, 2025)
Islam Nusantara is a reflective project that demands critical thinking, open dialogue, and the courage to remap the dynamics of religion in Indonesia in the era of globalisation and transnationalism. This study aims to describe in detail the discourse of Islam Nusantara in the current Indonesian context, including how the term, ideas, and implementation have developed from the local to the national level. This study focuses on conceptual and theoretical analysis through an in-depth literature review and cross-theory integration. The results confirm that the purity of Islam does not lie in rejecting culture, but in the ability to ignite divine values across diverse human realities. Islam Nusantara is a form of intelligent resistance to transnational purification that imprisons Islam in dogma, as well as a cultural project that affirms the sovereignty of Indonesian Muslims' interpretation of their own religion. In its reflective and open form, Islam Nusantara teaches that true piety is born of dialogue, not uniformity, and of wisdom that grows on one's own soil, not blind imitation of the centre of power. Thus, Islam Nusantara is not only a local discourse but a global offer on how religion can remain sacred without losing its humanity.